(untitled) (Afaq Lughawiyyah, 2024)
This research examines the phenomenon of intertextuality with folk proverbs in Naguib Mahfouz’s novels "Cairo Modern" and "Respected Sir". Folk proverbs, especially when embedded within literary works, hold significant importance in directing individuals towards the goals sought by the author or in conveying them to readers, thereby motivating recipients to pursue change and improvement. They strongly aid in self-construction, fostering self-confidence and self-esteem, as folk proverbs encapsulate long experiences in concise expressions, enabling readers to overcome various life challenges more effectively. Access to this Arab cultural heritage becomes crucial in shaping one’s history and future, enhancing readiness to make informed decisions. From this perspective, this research aims to analyze instances of intertextuality with folk proverbs in the mentioned novels, elucidating how Naguib Mahfouz employs these instances to craft remarkable literary works, showcasing the significant role of the renowned author in the literary field and his adeptness in borrowing, assimilating, or modifying texts. The research adopts a descriptive-analytical methodology, deemed most suitable and prevalent in social and human sciences. Findings reveal that intertextuality with folk proverbs has a significant presence in the novel al-Q?hira al-Jad?da and ?a?rah al-Mu?taram showcasing Naguib Mahfouz’s adeptness in handling this phenomenon. The research asserts that the novelist does not evoke these proverbs merely for embellishment, decor, or a display of poetic capabilities. Instead, he employs them purposefully to deepen his ideas and crystallize his vision on specific issues, seamlessly aligning with the artistic and stylistic structure of his novels.